2017
DOI: 10.1001/jamaoto.2017.1557
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Laryngoscopic Findings Associated With Response to Gabapentin in Patients With Chronic Cough

Abstract: In patients with chronic cough suspected to be related to vagal neuropathy, the odds of response to gabapentin are higher with the presence of VFMA noted on videostroboscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…However, precise roles of laryngeal dysfunction have not been confirmed in chronic cough [94]. Two observational studies suggested the potential benefit of gabapentin therapy for cough patients with abnormal motion of the larynx [95,96]. In clinical experience, it is suggested that speech language and pathology therapy including breathing technique education may be beneficial in chronic cough patients with comorbid laryngeal dysfunction [97].…”
Section: New Concepts To Consider In the Evaluation And Management Ofmentioning
confidence: 99%
“…However, precise roles of laryngeal dysfunction have not been confirmed in chronic cough [94]. Two observational studies suggested the potential benefit of gabapentin therapy for cough patients with abnormal motion of the larynx [95,96]. In clinical experience, it is suggested that speech language and pathology therapy including breathing technique education may be beneficial in chronic cough patients with comorbid laryngeal dysfunction [97].…”
Section: New Concepts To Consider In the Evaluation And Management Ofmentioning
confidence: 99%
“…Although current FDA-approved indications only include adjunct therapy for partial seizures and postherpetic neuralgia, gabapentin has numerous off-label uses, including the treatment of CRC. 75 Thus far, 12 current studies 54,56,[60][61][62][63][64][65][66][67][68][69] show favorable therapeutic effects of gabapentin; however, a standardized dose, optimal treatment duration, and longterm safety data have not been established. The American • PO amitriptyline 10 mg/day given QHS or 10 mL PO codeine/ guaifenesin 10 to 100 mg/5 mL every 6 hours standing dose while awake.…”
Section: Gabapentinmentioning
confidence: 99%
“…Two studies 54,67 saw therapeutic control only after the addition of amitriptyline 54 and botulinum toxin injections every 3 months 67 to gabapentin treatment. The findings of Lee and Woo 67 and Gilberto et al 69 suggest that patients with confirmed findings of motor neuropathy and/ or vocal fold motion asymmetry on laryngeal electromyography or videostroboscopy had an enhanced response to gabapentin therapy. In a case series by Ryan et al, 68 cough severity and cough quality of life improved in 2 patients with Arnold's nerve ear-cough reflex, a rare phenomenon where cough is triggered through mechanical stimulation of the ear.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…A cough is a reflexive inhalation and exhalation against a closed glottis resulting in the forceful expulsion of air as building pressure forces the glottis open. Cough can be classified as acute (lasting up to 8 weeks) or chronic (lasting greater than 8 weeks) [1] , [2] . While acute cough is often self-limited or requires minimal intervention, chronic cough is a common complaint that is often diagnostically and therapeutically challenging in the primary care, otolaryngology, pulmonology, or psychiatric settings.…”
Section: Introductionmentioning
confidence: 99%